مظاهر تعليمية الإعراب من خلال كتاب مغني اللبيب عن كتب الأعاريب لإبن هشام الأنصاري - علية, لحمير, عائشة عائشة (University of Eloued جامعة الوادي, 2019)
جاء هذا البحث ليتناول قضية نحوية مهمة ألا وهي مظاهر تعليمية الاعراب من خلال كتاب مغني اللبيب عن كتب الأعاريب لإبن هشام الأنصاري فما المقصود بتعليمية الاعراب؟ وما هي مظاهر تعليمية الاعراب عند ابن هشام حيث كان الهدف من هذه الدراسة هو:  تسليط الضوء على شخصية ابن هشام الانصاري العلمية التي جعلته بهذه المكانة المرموقة.  بيان مظاهر تعليمية الاعراب عن ابن هشام الانصاري. كما توصلنا في الاخير إلى العديد من النتائج أهمها:  ربط ابن هشام في كتابه الاعراب بالمعنى وأكد على قضية معرفة المعنى قبل الدخول في عملية الاعراب ونفى النظر إلى العلاقات السطحية واللفظية.  قسم المعنى إلى أصناف: معنى المفردة اي الوحدة والمعنى التركيبي في الجملة ثم المعنى العام وهو المعنى النصي أي العلم أي العلم بما يحيط النص من معان وأساليب. This research came to address the issue of grammatical task, which are educational aspects expressed through the book of singer El-Labib on the books of the Aarib of Ibn Hisham Al-Ansari What is meant by the teaching of the expression? And what are the manifestations of educational expression by Ibn Hisham where the objective of this study is: Highlighting the personality of Ibn Hisham Al-Ansari, who made him this prestigious position. Statement of educational manifestations expressed by Ibn Hisham Al - Ansari. We also reached a number of conclusions in the latter, the most important of which are: Ibn Hisham linked Ibn al-Hisham in his book Al-'Arab in the sense and stressed the issue of knowledge of meaning before entering the process of expression and denied consideration of superficial and verbal relations. Meaning: The meaning of singularity is the unity and the structural meaning in the sentence and then the general meaning which is the textual meaning ie science, which is the knowledge of what surrounds the text of meanings and methods..
Keywords: تعليمية الإعراب - مغني اللبيب - قضية نحوية; Educational Expression - singer Elbib - a grammatical issue